(untitled) (International Seven Journal of Multidisciplinary, 2023)
Utility systems are critical to the functioning of modern society, making their risk management essential to ensure safety, regulatory compliance, and service continuity. This article explores how audits, compliance, and business continuity planning (BCP) interrelate within utility environments, drawing on practical experience in implementing BCP and responding to international audits. Through an analysis of common challenges, best practices, and academic literature, the paper highlights the need for integrated governance, effective documentation, scenario-based testing, and strategic alignment with international standards such as ISO 22301 and ISO 31000. It emphasizes that resilience in utility systems depends not only on regulatory compliance but on organizational maturity and the institutionalization of continuity as a core value.